EFEKTIVITAS PENERAPAN PROGRAM KALIMASADA SEBAGAI UPAYA PERCEPATAN ADMINISTRASI KEPENDUDUKAN DI KECAMATAN ASEMROWO - Salsabila, Adinda Tarisa; Widiyarta, Agus (Jurnal Progress Administrasi Publik, 2024)
Decree of the Mentri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Number 63 of 2003 concerning general guidelines for the implementation of public services are the activities of service providers to meet the needs of the community. Although rapid population growth is administratively challenging, the government is expected to provide effective, fast, and satisfactory population administration services. But in practice population administration services often do not meet expectations, reflected in public complaints such as long queues, complicated procedures, and inaccurate time for issuing documents. This reflects the gap between expectations and implementation of public services, reflected in maladministration reports that continue to increase every year. This research applies a descriptive method with a qualitative approach, referring to the theory of effectiveness. The purpose of this study is to evaluate the effectiveness of the implementation of the Kalimasada program in Asemrowo sub-district. The Kalimasada program in Asemrowo sub-district as a step to accelerate population administration, can be considered quite effective based on four indicators of program effectiveness.   Keywords: Population; Administration; Effectiveness; Program